ANALISIS PERAN PENDIDIKAN DALAM PEMBANGUNAN EKONOMI ISLAM MELALUI SUMBER DAYA MANUSIA PASCA PANDEMI COVID - 19 - NIKITA ZULYAN BATUBARA; KHAIRINA TAMBUNAN (JURNAL ILMIAH KOHESI, 2022)
The existence of the Covid-19 virus has changed the whole world and felt its impact in various fields, especially education.All state leaders issued circulars regarding the teaching and learning process that started from face-to-face to online(distance learning). This makes students feel the impact themselves, including being unproductive. Moreover, developmentin Indonesia has declined due to this pandemic, so that there will be a reduction in productive and creative human resourcesto revive development through an Islamic economic perspective based on the Qur'an and Haditsh.